The effects of new firm formation on regional development over time: The case of Great Britain - Pamela Mueller; André J. van Stel; David J. Storey (Max Planck Institute of Economics, 2006)
This paper re-examines the link between new firm formation and subsequent employment growth. It investigates whether it is possible to have the wrong type of entrepreneurship - defined as new firm formation which leads to zero or even negative subsequent employment growth. It uses a very similar approach to that of Fritsch and Mueller (2004), confirming their findings that the employment impact of new firm formation is in three discrete phases. Then, using data for Great Britain, the paper shows the employment impact of new firm formation is significantly positive in England, but zero in Scotland where formation rates are much lower. It also shows that, in the low enterprise counties of GB, new firm formation has a negative effect on employment, implying that we find that the wrong type of entrepreneurship is possible.
Keywords: J23; L10; M13; R11; 330; New firm formation; employment growth; Great Britain; low entrepreneurial regions; Unternehmensgründung; Regionale Entwicklung; Beschäftigungseffekt; Großbritannien